Pendidikan Keamanan dan Perdamaian Berkelanjutan dalam Kurikulum Pendidikan Guru untuk Pembangunan Berkelanjutan: Persepsi Pendidik - Ogbu Eke, Eke; Onwubiko, Charles (At-Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
This study investigated security and sustainable peace education in teacher education curriculum for sustainable development, teacher educators’ perception. The study adopted survey design to determine AlvanIkoku Federal College of Education Owerri teacher educators’ perceptions on integrating security and sustainable peace education in teacher education curriculum for sustainable development. Researchers’ made attitude questionnaire titled” Teachers-educator Questionnaire onintegrating security and sustainable peace education in teacher education curriculum for sustainable development”was used for data collection. It had reliability coefficient of 0.86 determined using Cronbach Alpha.  The findings showed that teacher educators have positive perceptions onintegrating security and sustainable peace education in teacher education curriculum for sustainable development. It was recommended among others that relevant authorities in teacher education programme and teacher education curriculum planning should endevour to integrate security education in teacher education curriculum for effective sustainable development.